Niche partitioning based on nest site selection in the small carpenter bees Ceratina mikmaqi and C. calcarata - Vickruck, J.L.; Richards, M.H. (Animal behaviour, 2012)
Nest site selection can have important fitness consequences for bees: nest location and substrate influence conditions experienced by developing broods, and competition for nesting substrate influences the structure of bee communities. One approach to investigate how bees respond to limitations in nesting resources is to compare patterns of resource usage in the field to the outcome of choice experiments. If different species show overlapping resource preferences but nonoverlapping resource use, this suggests that interspecific competition results in resource partitioning. We investigated nest site selection and its fitness consequences in two closely related dwarf carpenter bee species (Ceratina mikmaqi and C. calcarata) in southern Ontario. Ceratina nests were found in the exposed pith of common teasel, Dipsacus fullonum, which grows in full sun, and in wild raspberry, Rubus strigosus, and staghorn sumac, Rhus typhina, which grow in shade. When experimentally given the opportunity to choose among equal numbers of nests in any combination of substrate (raspberry, teasel, sumac) and site (sunny, shady), both species preferred to nest in raspberry twigs in sunny sites. Collections from naturally occurring nests showed that C. calcarata nests occur primarily in the preferred substrate (raspberry), while C. mikmaqi nests occur in the preferred site (sun). Thus, competition for nesting substrate is partially offset by spatially partitioning nesting resources. Ceratina calcarata nesting in sunny microclimates produced larger and more offspring, and experienced less parasitism, whereas C. mikmaqi showed no effect of microclimate. Overall, this suggests that C. mikmaqi is the superior competitor for nesting substrate. ► Closely related species of carpenter bees reduced competition for nest sites through spatial partitioning. ► Both species (Ceratina mikmaqi, C. calcarata) experimentally preferred the same nesting substrate and site. ► Microclimate influenced offspring fitness while nest substrate did not.